Patients' perspectives on the ocular symptoms of facial paralysis after gold weight implantation - DURMUŞ KOCAASLAN, FATMA NİHAL; BAYRAMİÇLİ, MEHMET NURİ ÜMİT (ELSEVIER SCI LTD, 2008)
Upper lid loading for the treatment of lagophthalmos resulting from facial paralysis is a simple and effective procedure with relatively few side effects and complications. A detailed patient-based self assessment, focusing on subjective complaints after upper lid weight implantation is scarce. In this study, a population of facial palsy patients with lid weights is asked about their subjective complaints in order to find out the patients' point of view. Patients with upper lid weights were asked questions indicating the degree of soreness, tearing, redness, visual acuity, lid closing during the day, lid closing during steep, aesthetic appearance, artificial tear utilisation and outdoor comfort. All questions were evaluated by an analogue scale in reference to the opposite eye, where a score of '10' corresponds to the best outcome (no symptoms at all or appearance comparable to the contralateral eye) and a score of '1' corresponds to the worst outcome. Thirty patients filled in the questionnaire and 22 of them were seen in the outpatient clinic. The most pleasing result was obtained in the lid closing during the day (score 8.8 +/- 1.9), during sleep (7.7 +/- 3.0) and in the aesthetic appearance of the eye (score 7.6 +/- 2.7), whereas visual acuity received the lowest score (score 5.7 +/- 1.5). Complication and re-operation rates were 23% and 13%, respectively. In conclusion, upper lid weights solve the problem they are used to address. They provide a satisfactory lid closure and aesthetic appearance in the patients' point of view. However, the ocular symptoms of facial paralysis still persist to some extent and the procedure is not without its complications. (C) 2007 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Facial paralysis; Paralytic lagophtalmos; Lid weight; Patient satisfaction; Complication; EYELID WEIGHTS; NERVE PALSY; LAGOPHTHALMOS; MANAGEMENT; MORBIDITY; INSERTION